Propriedades magnéticas de nanoestruturas de Pd adsorvidas em Fe/Ir(111). - WEYL, Artemísia de Souza (2023)
In this work, we focus on the study of magnetic properties of a system composed by nanostructures of Pd on a Fe monolayer on Ir(111). We used the RS-LMTO-ASA (Real Space - Linear Muffin-Tin Orbital - Atomic Sphere Approximation) ab – initio method based on density functional theory (DFT). We have studied systems composed from one to seven atoms of Pd, with different geometries on the Fe/Ir(111) surface. The induced magnetic moment values on Pd varied from 0,35µB to 0,73µB. We have also calculated the exchange interaction on Pd-Fe atoms and the magnetic configuration of the systems, where we have found ferromagnetic states and non-collinear configurations, depending only on the system geometry.